PENERAPAN PENDEKATAN PROBLEM SOLVING DISERTAI SPEED TEST DALAM PEMBELAJARAN BIOLOGI PADA KELAS XI IPA SMAN 9 PADANG - Sandri, Vaulina Eka; Sudirman, Sudirman; Megahati, Megahati (STKIP PGRI Sumbar, 2013)
ABSTRACTÂ Biology is one of the areas of science and technology. The material of Biology being learning compulsory education, furthermore the government made great efforts to improve the quality of education such as curriculum improvement, adding educational facilities, and conducting workshops with teachers. But in fact, the result of studentsâ assignment in learning Biology at SMAN 9 Padang is lower, it is because students prefer to ask friends if they are not familiar with the concept given and have difficulty in doing the assignment. This study aims to determine the application of the learning outcomes approach accompanied Speed Test Problem Solving in Biology learning in class XI Science SMAN 9 Padang. This researched was an Experiment with the study designed Randomized Control Group Only Design. The population in this researched were all of subjects research which approached that uses the application of Problem Solving with Speed Test . This researched to know isÂ Â the application of Problem Solving approach accompanied Speed Test in Biology lesson in class XI Science SMAN 9Padang . The class XI IPA 3 as the experimental class material Food In Human Digestive System consists of the students 34 students , while the control class to use Conventional learning or learning Â and interview by using the same material that consists of 32 students. This researched using purposive sampling as technique of sampling. This researchedÂ used a test of student learning outcomes as instrument . Techniques of data analysis in this researched by using a t-test, the results of the analysis conducted , obtained t 2.74 and 1.67 table therefore t count > t table , then the hypothesis is accepted . The average value of 80.95 experimental class and the control class average 63.31 . It can be concluded that the learning outcomes of students taught with the application of Problem Solving approach accompanied Speed Test can be increased in Biology learning in class XI Science SMAN 9 Padang school year 2012/2013 .Â